Alexei Navalny’s Opposition Movement and Its Impact on the Political Transition in Putin’s Russia - Wasielewski, Szymon (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2024)
In recent years, Alexei Navalny has emerged as the most prominent Russian oppositionist and the main critic of Vladimir Putin’s regime. He undertook extensive efforts aimed at building civil society in Russia. His uncompromising attitudeearned him recognition in the West, including Poland. Navalny’s critics pointed to his nationalist and imperialist views and the almost uncritical support for his activities often expressed by world leaders and international institutions. The main goal of the article is to analyze the Alexei Navalny’s opposition efforts as he sought to transform the Russian political system. The hypothesis suggests that despite numerous initiatives by Navalny’s supporters and the backing of the international community, his activities failed to bring about the expected changes on the Russian political arena. The tightening of Vladimir Putin’s regime led to an increased repression against citizens opposing the government, significantly hindering opposition’s efforts and ultimately contributing to Navalny’s death. Aleksiej Nawalny w ostatnich latach uważany był za najważniejszego rosyjskiego opozycjonistę oraz głównego krytyka reżimu Władimira Putina. Podejmował szeroko zakrojone działania zmierzające do budowy społeczeństwa obywatelskiego w Rosji. Swoją bezkompromisową postawą zyskał uznanie na Zachodzie, w tym w Polsce. Krytycy Nawalnego zwracali uwagę na jego nacjonalistyczne i imperialistyczne poglądy oraz niemalże bezkrytyczny stosunek dla jego działalności wyrażany często przez światowych przywódców i instytucje międzynarodowe. Celem artykułu jest analiza działalności opozycyjnej Aleksieja Nawalnego, który w swoich działaniach dążył do przemian rosyjskiego systemu politycznego. Jako hipotezę przyjęto założenie, zgodnie z którym działalność opozycjonisty, mimo podejmowania przez jego zwolenników licznych inicjatyw oraz poparcia środowiska międzynarodowego, nie przyniosła oczekiwanych zmian na rosyjskiej scenie politycznej. Zaostrzanie się reżimu Władimira Putina doprowadziło do wzrostu represji wobec obywateli sprzeciwiających się władzy, co w znacznym stopniu utrudniało prowadzenie skutecznej walki opozycyjnej oraz przyczyniło się do śmierci Nawalnego.
Ruch opozycyjny Aleksieja Nawalnego i jego wpływ na przemiany polityczne w Rosji Putina
Keywords: Navalny; opposition; Russia; regime; Putin; Nawalny; opozycja; reżim